2022
DOI: 10.1101/2022.05.29.493899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental transitions coordinate assembly of the Coxiella burnetii Dot/Icm type IV secretion system

Abstract: Coxiella burnetii is an obligate intracellular bacterial pathogen that has evolved a unique biphasic developmental cycle. The infectious form of C. burnetii is the dormant small cell variant (SCV) that transitions to a metabolically active large cell variant (LCV) that replicates inside the lysosome-derived host vacuole. A Dot/Icm type IV secretion system (T4SS), which can deliver over 100 effector proteins to host cells, is essential for the biogenesis of the vacuole and for intracellular replication. How the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…On the other hand, and despite several data processing trials, we could not resolve the cytoplasmic ATPase complex. A contemporaneous study on C. burnetii T4BSS used more than 7000 particles to generate an in situ average (46), but their structure also lacked the cytoplasmic complex suggesting that the C. burnetii T4BSS ATPase complex is either flexible or rarely associated. Earlier studies have shown that acidification of the CCV inside the host triggers the differentiation of SCVs into LCVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, and despite several data processing trials, we could not resolve the cytoplasmic ATPase complex. A contemporaneous study on C. burnetii T4BSS used more than 7000 particles to generate an in situ average (46), but their structure also lacked the cytoplasmic complex suggesting that the C. burnetii T4BSS ATPase complex is either flexible or rarely associated. Earlier studies have shown that acidification of the CCV inside the host triggers the differentiation of SCVs into LCVs.…”
Section: Resultsmentioning
confidence: 99%
“…While T4ASS is known to harbor extracellular pili containing VirB2 and VirB5 proteins (48), the T4BSS has no putative pilin candidates and there are no reports of this system producing a pilus. Previous studies proposed that the C. burnetii T4BSSs interact with the CCV membrane using short tethers that could facilitate translocation of T4BSS effectors (49), and a contemporaneous study also reported short filamentous densities between the bacterial OM and the CCV membrane (46). It is possible that the short tubular structures above some T4BSS particles are used to establish such an intimate contact between the bacterial OM and CCV membrane.…”
Section: Discussionmentioning
confidence: 99%